THE UNDERGRADUATE MEDICAL STUDENTS’ PITFALLS IN EYE EXAMINATION STATION OF OBJECTIVE STRUCTURED CLINICAL EXAMINATION - Widyandana Doni; Angela Nurini Agni; Agus Supartoto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: High prevalence of eye disorders in Indonesia requires medical doctors to be skillful and well trained in ophthalmologic examination. Undergraduate medical students usually start their clinical simulation practice and ophthalmology assessment in a safe learning environment. Skill laboratory as the learning facility should be evaluated and improved regularly. This study aimed to evaluate student’s pitfalls in the eyes OSCE station. Methods: Descriptive analytic study involving Objective Structured Clinical Examination (OSCE) eye examination station score from 1st - 4th year undergraduate medical students batch 2010 in Faculty of Medicine, Universitas Gadjah Mada, Indonesia (n=516). All checklists’ scores were analyzed based on particular sub-scales in every examination topic to explore the most pitfalls made by students in eye examination station during OSCE. Results: The order average value of each subscale in OSCE are: Doctor patient interaction (88.42), History taking skills (82.44), Professionalism (76.43), Physical Examination (74.62), Diagnosis (60.68), Management of Pharmacotherapy (54.70). The percentage of failed-students (scores <70) in 1st-4th year OSCE based on topics skills were Year 1: Visual field (5.08%), Visual acuity (14.21%), Anterior Segment (2.54%). 2nd year: IOP by palpation (24.38%), Visual acuity (9.38%), Anterior Segment (29.38%). Year 3: visual field (4.94%), IOP by palpation (2.47%), Visual acuity (12.35%), Anterior Segment (7.41%), Posterior Segment (22.22%). Year 4: Comprehensive eye exam (17.95%). Conclusions: Students mostly challenged in the skills of diagnosis establishment and pharmacological management. The highest number of failed students in each year OSCE vary from each year. 1st year failed most at visual acuity examination, 2nd year was anterior segment examination and 3rd year was posterior segment examination. Those three skills need to be enhanced systematically. Keywords: OSCE, pitfall pattern, eye examination, undergraduate students, skill laboratory